RELATIONSHIP BETWEEN ANTI-CCP ANTIBODIES AND DISEASE ACTIVITY, RADIOLOGICAL DAMAGE IN PATIENTS WITH RHEUMATOID ARTHRITIS - Ümit Dündar; Deniz Evcik; Tuncay Çakır; Orhan Aktepe; Mustafa Altındiş; Vural Kavuncu (Archives of Rheumatology, 2005)
Recently, clinical value of antibodies against cyclic citrullinated peptide (Anti-CCP) was studied in the patients with rheumatoid arthritis (RA). Positivity of Anti-CCP antibodies showed a relation with erosive arthritis and radiological damage. The aim of this study was to investigate the relationship between Anti-CCP antibodies and disease activity and radiological damage in patient with RA. Thirty seven patient (12 M/ 25 F) with RA enrolled in this study. After physical examination, all patient were evaluated for clinical, radiological and laboratory parameters. Clinical parameters included the visual analog scale (VAS) and disease activity score(DAS) 28. In laboratory; erythrocyte sedimentation rate (ESR), C-reactive protein (CRP), rheumatoid factor (RF) and Anti-CCP levels were measured. Radiological damage was assessed by using modified Larsen score. RF were positive in 15 patients (%40,5) and negative in 22 (%59,5) patients. Anti-CCP were positive in 24 patient(%64,9) and were negative in 13 (%35,1) patients. There were no statistically significant differences between the mean values of ESR, CRP, DAS 28 and VAS scores, modified Larsen scores of the Anti-CCP positive and negative patients (p>0,05). As a result, although we could not find any significant relation between Anti-CCP antibodies and clinical and radiological parameters of RA, further studies with larger groups are needed to investigate this association.